Datura innoxia plants hydroponically-inoculated with Agrobacterium rhizogenes display an enhanced growth and alkaloid metabolism. (December 2018) - Vu, Thi Dao; Jousse, Cyril; Pawlicki-Jullian, Nathalie; Schiltz, Séverine; Nguyen, Thi Kieu Oanh; Tran, Thi Le Minh; Bouquet, Laure-Anne; Hehn, Alain; Boitel-Conti, Michèle; Moussaron, Julie; Biteau, Flore; Assaf-Ducrocq, Corinne; et al.
Graphical abstract: Highlights: Agrobacterium rhizogenes added in the nutrient solution of hydroponic Datura innoxia medicinal plant enhances its growth. Co-culture of hydroponic Datura with A. rhizogenes increases tropane alkaloid levels in roots and leaves. Transformation events occur, leading to what we call "semi-composite plants". Abstract: Background: The production of secondary metabolites through the culture of entire plants is of great interest. Soilless culture, such as hydroponics, enables the control of plant growth and metabolism. Specific environmental conditions must be developed to maximize the productivity of medicinal plants used as efficient natural bioreactors. Methods: The nutrient solution of newly established hydroponic cultures of Datura innoxia Mill. were inoculated with Agrobacterium rhizogenes ( A.r. ) wild strains (TR7, TR107, 11325 or 15834). Growth and the alkaloid contents of roots and aerial parts were analyzed. Axenic cultures were also performed with modified TR7 strains containing the egfp or gus reporter gene. In vitro isolated root cultures enabled the phenological and molecular demonstration of gene transfer. Results: A.r. TR 7 led to a greater improvement in plant secondary metabolism and growth. Positive expression of the reporter genes occurred. Isolation and subculture of some of the roots of these plants showed a hairy root phenotype; molecular tests proved the transfer of bacterial genes into the roots isolated from the plants. Conclusions: Hyoscyamine and scopolamine productivity is enhanced after A.r. inoculation in the nutrient solution of hydroponic plants. Transformation events occur in the original roots of the plants. This leads to chimeric plants with a part of their roots harboring a hairy root phenotype. Such semi-composite plants could be used for successful specialized metabolite bioproduction in greenhouses.